Identifikasi Potensi Daerah Berbasis Partisipasi untuk Pemberdayaan Masyarakat Belitung Timur - Wahyudi, Triyono Arief; Iskandar, Donant Alananto (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
East Belitung Regency has significant natural, social, and economic potential that remains underutilized for improving community welfare. This community service activity aimed to map regional potential and problems while formulating priority programs for participatory local economic development. Using participatory mapping with a Rapid Appraisal Method approach, data were collected through structured and in-depth interviews, field observations, and Focus Group Discussions (FGDs). Respondents were selected using snowball and purposive sampling, involving village officials, community leaders, youth, women, and local business actors. The activity was conducted on October 5, 2024, as a collaboration between universities, businesses, and the community. Five priority programs were identified: local resource-based crafts, digital MSME strengthening, fisheries and processed seafood development, educational tourism and environmental preservation, and integrated homestead farming with food security. These programs align with community needs and regional potential, providing a foundation for targeted, inclusive, and sustainable empowerment initiatives in East Belitung Regency